Impact of atopic dermatitis on renal dysfunction: insights from patient data and animal models - Ikeda, Arisa; Peng, Ge; Zhao, Wanchen; Abudouwanli, Alafate; Ikeda, Shigaku; Niyonsaba, François; Suzuki, Yusuke (Frontiers in Immunology, 2025)
IntroductionAtopic dermatitis (AD) is a chronic inflammatory skin disease characterized by pruritus, immune dysregulation, and compromised skin barrier function. Although there are some reports that indicate a link between AD and chronic kidney disease (CKD), the prevalence and underlying mechanism of the association between AD and CKD are still unclear. We aimed to clarify the mechanism underlying the association between AD and CKD using an AD-like mouse model.MethodsHuman serum and urine samples from adults in the U.S. were analyzed using data from the National Health and Nutrition Examination Survey (NHANES). An AD-like mouse model was established by repeatedly applying 2,4-dinitrochlorobenzene to the backs and ears of the mice. Kidney inflammation and podocyte function were evaluated via PAS and H&E staining, immunofluorescence staining, and electron microscopy.ResultsWe found that compared to healthy subjects in the NHANES cohort study, patients with AD had altered kidney function. AD-like model mice exhibited albuminuria and renal dysfunction one to three months after the induction of AD. In addition, there were remarkable decreases in triglyceride and very-low-density lipoprotein levels and increases in low-density lipoprotein and non-high-density lipoprotein levels in AD-like model mice. After histological staining of the kidneys of AD-like model mice, macrophage and neutrophil infiltration was detected, and the foot process effacement of podocytes was observed via electron microscopy. In addition, the gene expression of slit diaphragm- and podocyte-related proteins such as nephrin, podocin, and synaptopodin decreased, whereas the gene expression of inflammatory mediators such as S100A8 and S100A9 increased.DiscussionFollowing improvements in skin inflammation, alleviation of albuminuria, renal dysfunction and dyslipidemia were observed. These findings suggest that AD-related cutaneous inflammation is associated with albuminuria and podocyte dysfunction.